2021
DOI: 10.3390/buildings11020060
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Influence of Nano and Micro Particles on the Workability and Mechanical Properties of Mortar Supplemented with Fly Ash

Abstract: In this study, the effects of micro‐Al2O3 (MA) and nano‐Al2O3 (NA) on the mechanical properties and durability performance of a mortar containing fly ash (FA) were investigated. In the first step, MA and NA were added to the mortar (as a cement replacement) at dosages of 0%, 5%, 10% and 15% by weight. The flowability of the mixture containing NA and MA showed a dosage‐dependent behavior, and the addition of MA resulted in a higher flow spread compared with NA. The flow spread increased at 5% (for both NA and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The combination of MS and MK has a positive impact on the strength and durability of concrete, and the findings revealed that it can lead to an increase in the water demand [ 45 ]. Moreover, the presence of NS in the ternary binder consisting of OPC-MK-NS increased the consistency ( Fig 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of MS and MK has a positive impact on the strength and durability of concrete, and the findings revealed that it can lead to an increase in the water demand [ 45 ]. Moreover, the presence of NS in the ternary binder consisting of OPC-MK-NS increased the consistency ( Fig 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it was found that when MS was added as replacement of cement to make the ternary binder along with MK, the water demand increased. The combination of MS and MK has a positive impact on the strength and durability of concrete, and the findings revealed that it can lead to an increase in the water demand [45]. Moreover, the presence of NS in the ternary binder consisting of OPC-MK-NS increased the consistency (Fig 2A).…”
Section: Fresh Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…This can be attributed to the high specific surface of them, which absorbs water and contributes to increased water demand to maintain mixing and control the concrete's workability. (5) M. Seifan et al (26) observed that workability of all dosages of Al₂O₃ samples was just slightly a lesser than workability of the samples without Al₂O₃ due to high ratio of surface area to volume. M. Khopade et al (27) reported that the mixes that contained Al₂O₃ had a lower slump than the controlled specimens owing to the softness of the Al₂O₃, which enhanced the properties of the concrete like filling, bonding, and evenness and also reduced the diffusion diameter of the concrete in slump flow.…”
Section: Results Of Fresh Propertiesmentioning
confidence: 99%
“…An investigation of the effect of micro-Al 2 O 3 [MA] and nano-Al 2 O 3 [NA] on the mechanical characteristics and durability of a fly ash mortar [FA] was conducted by Seifan et al (26). A portion of the cement in the mortar was substituted with MA or NA at the amounts of 0%, 5%, 10%, and 15%.…”
Section: Ogólna Technika Przygotowania Nanocząstek Feni 3 Mnpmentioning
confidence: 99%